Leasing in the Supreme Court - Pásara, Luis (1978)
At the end of 1976, the Peruvian Supreme Court of Justice issued a series of resolutions in which it established different criteria of application and introduced a novel interpretation. Therefore, the aim of this paper is to analyze the interpretative changes that appeared in the court to determine their applicability. To this end, the arguments and interpretative methods used by the judges to resolve the lease trials are detailed. This will make it possible to evaluate the application of the law and the legitimacy of the interpretation performed. In this way, it is concluded that the judges have legitimacy in their innovative interpretation, which allows the creation of jurisprudence as an effective source of law.